Simulating the Evolution of Qiangtang No. 1 Glacier in the Central Tibetan Plateau to 2050 - Li, Yemeng; Tian, Lide; Yi, Yang; Moore, John C.; Sun, Sainan; Zhao, Liyun (Arctic, Antarctic, and Alpine Research, 2017)
Few simulations of typical Tibetan Plateau glacier response to climate warming have been made, despite the glaciers' importance as water supplies in an arid region. Here we apply a three-dimensional thermomechanically coupled full-Stokes ice dynamics model to simulate the evolution of Qingtang No. 1 Glacier, a representative glacier in the central Tibetan Plateau. A degree-day model along with snow temperature and precipitation estimates based on nearby observations are used to estimate surface mass balance (SMB) over the past three decades. The resulting SMB gradients and equilibrium-line altitude (ELA) sensitivity to air temperature are used to parameterize the SMB in the future. We use the ice-flow model to simulate glacier evolution from 2013 to 2050. Simulated within-glacier temperatures and present-day glacier terminus retreat rates are in reasonable agreement with previous observations. Forcing the glacier model with the historical warming trend of 0.035 °C a-1 and a warming projection from the high-resolution regional climate model (RegCM3) under the A1B scenario for the period 2013-2050 leads to substantial retreat and ice loss, and large increases (110%-155%) in annual water runoff. Losses of 11%-18% in area and 19%-30% in volume are predicted over the next four decades, with the warmer RegCM3 scenario giving larger rates of loss. Sensitivity of glacier change to the parameters in SMB profiles are also assessed.